Jenis Kecerdasan dan Kinerja Audit: Gender sebagai Variabel Moderasi - Syarah Sefty Andraeni; Nurhastuti Kesumo Wardhani (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to assess the effect of different types of intelligence on auditor performance with gender as a moderator. The types of intelligence include emotional intelligence and adversity. The research method used is quantitative with a population that includes 121 auditors who work in the Jakarta area Public Accounting Firm and uses the Partial Least Square SEM (PLS-SEM) method to assess the effect of the independent variables on the dependent variable. This research on the adversity intelligence variable uses the measurement developed by Stoltz (1997). This study shows that emotional intelligence and adversity affect audit performance and gender can moderate the independent variables. Auditors who have a qualified level of emotional intelligence can manage their emotions appropriately and know exactly what to do when faced with various situations so that their performance levels can be stable and effective. When an auditor has a high level of adversity intelligence, he will be able to survive in situations of unreasonably dense activities and working hours. This research is useful as a reference for auditors or other professions to be able to find out that there are psychological factors that can affect performance and add to the literature and recommendations for policy makers regarding gender equality in Indonesia.